Kaolinite sludge dewatering using different coagulants from Moringa oleifera seeds - Qabas, Marwan Abdulazeez; Jami, Mohammed Saedi; Alam, Md. Zahangir; Iwata, Masashi (2017)
In this research, seven sets of coagulants were prepared from Moringa oleifera (MO) seeds and applied on kaolin suspension as synthetic sludge model. The first form is crude MO seeds powder without any treatment, while the second is defatted MO seeds powder. The third form was prepared by mixing the defatted seeds powder with distilled water for the extraction of bioactive compounds. The other coagulant forms were prepared using salts extraction (1 Molar), which are NaNO3, KCl, KNO3, and NaCl. Dewatering efficiency was evaluated through specific resistance to filtration (SRF) and supernatant turbidity measurements. Results showed that the extraction by NaNO3 and NaCl have the highest dewaterability compared to the other coagulant forms. MO seeds extract by NaNO3 was recorded supernatant turbidity of 29.3 NTU and SRF of 1.06x1011 m/kg at 600 mg/L dosage. The same SRF value was obtained with NaCl extraction at the same dosage, while the supernatant turbidity was recorded 31 NTU. Nevertheless, untreated and defatted powder forms have low sludge dewaterability at 600 mg/L and no dewaterability at low dosage. The extraction of bioactive compounds from MO seeds using NaNO3 and NaCl is very efficient, and the final product can be used as natural sludge conditioner.